Macrophage interaction with paracoccidioides brasiliensis yeast cells modulates fungal metabolism and generates a response to oxidative stress (2015)
ABTRACT: Macrophages are key players during Paracoccidioides brasiliensis infection. However, the relative contribution of the fungal response to counteracting macrophage activity remains poorly understood. In this work, we evaluated the P. brasiliensis proteomic response to macrophage internalization. A total of 308 differentially expressed proteins were detected in P. brasiliensis during infection. The positively regulated proteins included those involved in alternative carbon metabolism, such as enzymes involved in gluconeogenesis, beta-oxidation of fatty acids and amino acids catabolism. The down-regulated proteins during P. brasiliensis internalization in macrophages included those related to glycolysis and protein synthesis. Proteins involved in the oxidative stress response in P. brasiliensis yeast cells were also up-regulated during macrophage infection, including superoxide dismutases (SOD), thioredoxins (THX) and cytochrome c peroxidase (CCP). Antisense knockdown mutants evaluated the importance of CCP during macrophage infection. The results suggested that CCP is involved in a complex system of protection against oxidative stress and that gene silencing of this component of the antioxidant system diminished the survival of P. brasiliensis in macrophages and in a murine model of infection.